Pemanfaatan Media Pembelajaran Digital sebagai Strategi Pembelajaran Interaktif di Era Digital: Studi Pustaka - Ismawatul Hasanah; M Misbahudholam (Kampus Akademik Publiser, 2026)
This article aims to describe the use of digital learning media as an interactive learning strategy in the digital era. The study applies a descriptive qualitative method with a literature study approach. The data sources used in this article consist of national journal articles published within the last ten years and relevant to digital learning media, interactive learning, online learning platforms, multimedia, Android based media, Canva, Google Sites, Wordwall, YouTube, Google Meet, and Zoom. Data were collected through literature tracing, reading, note taking, classification, and interpretation of relevant findings. The results of the study indicate that digital learning media can support more interactive learning by presenting materials in visual, audiovisual, flexible, and participatory forms. Digital learning media also helps teachers create learning activities that are more varied and encourages students to be more involved in the learning process. However, its use still faces several challenges, such as limited facilities, unequal internet access, teacher digital competence, and the risk of distraction when digital devices are not used properly. Therefore, digital learning media needs to be selected based on learning objectives, student characteristics, material needs, and school readiness.